The role of thin filament sarcomeric proteins tropomyosin 1 and cardiac troponin T in the developing heart - England, Jennifer (2016)
The heart is the first functioning organ to develop during embryogenesis to maintain the growing embryo with oxygen and nutrients. However, cardiogenesis is a complex but well-regulated process, and any changes to this regulation can result in detrimental defects of the heart. For many years sarcomeric proteins have been associated with a range of cardiomyopathies and in more recent years are known to been involved in congenital heart defects (CHDs). To date, tropomyosin 1 (TPM1) and cardiac troponin T (TNNT2) have been associated with cardiomyopathies but never with CHDs. These two genes are important regulatory proteins of the thin filament of the sarcomere and vital for correct contraction and force generation within cardiomyocytes. To investigate a role for TPM1 and TNNT2 in the early developing heart, using the chick as an animal model, antisense oligonucleotide morpholino technology were utilised to manipulate both genes in ovo. The gross anatomical structures, ultrastucture and molecular functions of the treated hearts were analysed to determine if the morpholino treatment resulted in any developmental abnormalities. In addition, the TPM1 gene, including introns, was sequenced in a cohort of 380 patients with a range of congenital heart anomalies. In the TPM1-morpholino treated hearts, atrial septation and ventricular chamber maturation via the production of trabeculae were affected. Stereological analysis of these hearts revealed a reduction in the proportion of myocardium in the ventricular chamber along with increased luminal size. In addition, TPM1-morpholino treatment had an effect on myofibril maturation in vitro, as well as causing increased apoptosis in the developing ventricle and atrial septum. Four genetic variants of TPM1 were identified in the patient cohort; I130V, S229F, IVS1+2T>C and GATAAA/AATAAA in the polyadenylation signal. In silico analysis predicted the missense mutations to be disease causing. In vitro functional analyses of the IVS1+2T>C mutation that the IVS1+2T>C mutation resulted in abnormal splicing of the TPM1 pre-mRNA. TNNT2-morpholino treatment affected the growth of the atrial septum. However, the sarcomere appeared normal in this treatment group. Stereological analysis also revealed normal cardiac proportions except for the atrial chamber, which was reduced in size. The abnormal phenotypes observed in the TPM1 and TNNT2 treated groups may be a result of altered haemodynamics within the developing heart. Further studies such as in situ hybridisation of markers of haemodynamics may elucidate this role in the future. The abnormal splicing observed in the IVS1+2T>C may be a contributing factor to CHD in man and therefore, indicates that sarcomeric proteins are important for the future screening of potential contributing factors to CHDs.